The Association of Red Blood Cell Distribution Width to Platelet Count Ratio and 28-Day Mortality of Patients with Sepsis: A Retrospective Cohort Study - Ge S; Lin S; Zhang L; Zeng M (Dove Medical Press, 2020)
Shanhui Ge, Shan Lin, Lishan Zhang, Mian Zeng Department of Medical Intensive Care Unit, The First Affiliated Hospital of Sun Yat-sen University, Guangzhou, Guangdong 510080, China; Institute of Pulmonary Diseases, Sun Yat-sen University, Guangzhou, Guangdong, People’s Republic of ChinaCorrespondence: Mian ZengDepartment of Medical Intensive Care Unit, The First Affiliated Hospital of Sun Yat-sen University, No. 58 Zhongshan Road 2, Guangzhou, Guangdong 510080, People’s Republic of ChinaEmail zengmian@mail.sysu.edu.cnBackground: Sepsis is a life-threatening and inflammatory disease with high morbidity and mortality. Red blood cell distribution width to platelet count ratio (RPR) was known as an inflammatory biomarker and was related to poor outcomes of various diseases.Aim: This study was intended to explore the association between RPR and mortality of sepsis patients.Methods: A retrospective cohort study was undertaken in patients with sepsis, and the data were collected from a public database called Medical Information Mart for Intensive Care III (MIMIC-III). The primary outcome was 28-day mortality while the secondary outcomes were 90-day mortality and ICU mortality. Multivariable regression analyses, as well as interaction and stratified analyses, were conducted to investigate the relation between RPR and sepsis mortality.Results: In total, we enrolled 7531 patients with 1316 deaths. RPR was independently correlated with 28-day mortality (per 0.1 increase: HR=1.04; 95% CI 1.02– 1.06), 90-day mortality (per 0.1 increase: HR=1.04; 95% CI 1.03– 1.06) and ICU mortality (per 0.1 increase: OR=1.06; 95% CI 1.02– 1.10). Twenty-eight-day survival was worse in the high RPR (≥ 0.134) group according to the Kaplan–Meier curve analyses (Log rank test, p< 0.001). In stratified analyses, Sequential Organ Failure Assessment (SOFA) score and length of ICU stay had interactive effects with the high RPR (≥ 0.134) group on 28-day mortality.Conclusion: RPR is a novel biomarker that indicates poor prognosis of sepsis patients. Clinicians are required to pay more attention to those patients with high RPR.Keywords: ICU, sepsis, prognosis, inflammatory marker, MIMIC-III